Vrana-See, Kroatien. Bauhistorische Untersuchungen zu den befestigten Höhensiedlungen in der kroatischen Vrana-See-Region (Zadar). Die Arbeiten des Jahres 2021 - Ley, Judith; Lang, Franziska (e-Forschungsberichte des DAI, 2023)
The architectural research on the ancient hilltop settlement of Zamina and other fortified gradines in its vicinity was supported by a research grant from the German Archaeological Institute (DAI). It is integrated into the German-Croatian research project of the Romano-Germanic Commission (RGK) »From the Karst Mountains to the Sea. Settlement forms, spatial development and use from the Iron Age to Late Antiquity at Lake Vrana«. In October 2021, a joint three-week building survey campaign was conducted by various project participants, ranging from hand measurements to 3D LiDAR scans. The construction research clearly shows how the interdependencies of the regional natural, anthropogenic, and economic conditions determined the settlement morphology.